Impact of Exchange Rate on Trade Deficit and Foreign Exchange Reserve in Nepal: An Empirical Analysis - Adhikari, Deepak (NRB Economic Review, 2018)
The objective of the study is to examine the impact of exchange rate on trade deficit and foreign exchange reserve in Nepal. The hypotheses of the study are: (a) there is no significant positive association between nominal exchange rate and foreign exchange reserve and (b) there is no significant relationship between nominal exchange rate of Nepalese rupee with US dollar and trade deficit. As empirical analysis shows that one percentage point depreciation of the Nepalese rupee (NPR) with respect to US dollar results in an (a) increase in reserve by 0.82 percentage points and (b) decline in trade deficit by 0.75 percentage points, the null hypotheses are rejected, thus suggesting that maintaining NPR undervalued with US dollar can improve trade deficit and increase foreign exchange reserves. However, because of pegging with Indian currency, NPR sometimes appreciates in line with Indian currency. This situation could be counterproductive for improving trade deficit and increasing foreign exchange reserve of Nepal. In conclusion, considering the external sector stability as one of the major policy objectives, exchange rate policy can be fine-tuned to correct the trade deficit and maintain adequate foreign exchange reserve to sustain imports and service external debt.